De' Green Surprise Sdn Bhd / Sharif Azmi Abdurahman ... [et al.] - Abdurahman, Sharif Azmi; Darwing, Heril; Yarabe, Mohammad Farizal; Mansur, Jumarang (2009)
De' Green Surprise is a business that is focusing on producing snack based on cendol. Our products are variety and it's basically made from cendol. The cendol is being on demand where we can found in every state in Malaysia. We are concerning of the new receipt of cendol, therefore it can be commercialized widely in our country. We are also trying to make this traditional snack to be one of the main menu in every single meal by our added value of recipe. Our market target is focusing on every stage of ages and since it is the traditional snack, we try to attract the youngsters to appreciate our local food instead of buying the western food. For the time being we are trying to commercialize our product locally because it needs time big investment to enter global market. Last but not least, we hope our product will be accepted by everyone and indirectly can contribute to the national income ever.